The Pocket Idiot's Guide to Spanish for Health Care Professionals : Hundreds of Phrases to Help You Communicate Effectively with Spanish-Speaking Patients /: Hundreds of Phrases to Help You Communicate Effectively with Spanish-Speaking Patients. (2004) - Sullivan, K. D; Prof, Castillo, Richard P
No abstract available